COMPARISON AND COMPARATIVE MARKERS IN DAN EAST - Gildas, Gondo Bleu (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
This paper deals with "Comparison and comparative markers in (Dan East)", and puts in the light over the readers the morphemes used to draft a comparison in the Dan-language and more specifically in (Dan East). Field investigations and analyses of the corpus detect two types of comparison in (Dan East): The restrictive comparison and the broad comparison. The restrictive comparison does not include comparative morpheme and comparing while the broad comparison includes comparative morphemes and comparators. As far as the broad comparison is concerned, two types of comparison are noted: simple comparison and comparison of superlatives. Each of the two groups has comparative morphemes that vary from one category of comparison to another. Thus, the comparatives selected within the simple comparison are: inferiority (ká... ɓà), equality (káɗɛ̀... ɗɤ́) and superiority (ká... tȁ). As for the comparison of superlatives, inferiority is manifested by: relative (dèdèwó) and (+/-H + adjective (diminutive/augmentative)), inferiority (foc + (-/+) H + diminutive adjective), superiority (foc + (-/+) H + adjective augmentative) and excessive superlative (Adjective (diminutive/augmentative) + gbɪ̋).